Handbook of human factors and ergonomics - Salvendy, Gavriel (Hoboken, NJ : Wiley, 2012)
"This is the fourth edition of the market-leading reference for human factors and ergonomics researchers, academics, and professionals. Editor Gavriel Salvendy, a well-known and respected authority, has assembled the top thinkers and practitioners from throughout the world to update this volume. It features new coverage of voice communication, multi-modal design, human-robot communication, call center design and operation, design of electronic games, and much more.Plus new and expanded coverage of Human Error and Human Reliability Analysis"--
"This is the Fourth Edition of the market leading reference for human factors and ergonomics researchers, academics, and professionals. Well-known and respected authority, editor Gavriel Salvendy has assembled the top thinkers, and practitioners from throughout the world to update this volume. New coverage of voice communication; multi modal design; human-robot communication; call center design and operation; design of electronic games and much more"--
Includes index.
Keywords: Human engineering; TECHNOLOGY & ENGINEERING / Industrial Engineering